Influence of the beam profile crosslinking setting on changes in corneal topography and tomography in progressive keratoconus: Preliminary results - Herber, Robert; Kunert, Kathleen S; Veliká, Věra; Spoerl, Eberhard; Pillunat, Lutz E; Raiskup, Frederik (Journal of cataract and refractive surgery, 2018)
PURPOSE: To evaluate the effect of accelerated corneal crosslinking (CXL) with a "higher peripheral intensity" profile setting compared with a standard "top hat" profile setting performed using different CXL systems. SETTING: Department of Ophthalmology, University Hospital Carl Gustav Carus, Dresden, Germany. DESIGN: Retrospective case series. METHODS: Eyes from patients with progressive keratoconus were included. Group 1 included eyes treated with the higher peripheral intensity profile. Group 2 included eyes treated with the top hat profile. Accelerated CXL was performed based on the modified Dresden protocol (9 mW/cm2, 10 minutes). Corneal-topography and tomography are characterized using the Pentacam Scheimpflug system. RESULTS: The study comprised 45 eyes (25 eyes in Group 1, 20 eyes in Group 2) from 45 patients. The keratometry (K) at the apex (maximum K) decreased significantly from 54.95 diopters (D) ± 6.73 (SD) to 53.21 ± 6.05 D for Group 1 (P < .001) and from 57.29 ± 7.16 D to 56.48 ± 6.88 D for Group 2 (P = .01). In Group 1, flat K (K1) and steep K (K2) decreased significantly after treatment (P < .05). The thinnest corneal thickness decreased significantly by -17.5 ± 21.9 μm (P = .001) in Group 1. In Group 2, no significant flattening was observed in K1 and K2 (P > .05), and the thinnest corneal thickness showed a slight but not significant thinning (P = .097). CONCLUSIONS: In Group 1 (the higher peripheral intensity group), the corneal topographic and tomographic parameters improved significantly after accelerated CXL. The higher peripheral intensity profile effect on keratoconic cornea flattening seemed to be more pronounced compared with the top hat profile.
Keywords: dospělí; Corneal Pachymetry; Female; Adult; ženské pohlaví; rohovka; mladý dospělý; Corneal Topography; Collagen; Adolescent; Keratoconus; Cornea; časové faktory; Time Factors; lidé; kolagen; Photochemotherapy; riboflavin; Photosensitizing Agents; Cross-Linking Reagents; následné studie; pachymetrie rohovky; fotosenzibilizující látky; reagencia zkříženě vázaná; retrospektivní studie; Follow-Up Studies; Male; rohovková topografie; Young Adult; lidé středního věku; mužské pohlaví; zraková ostrost; Visual Acuity; fotochemoterapie; Retrospective Studies; keratokonus; Middle Aged; mladiství; Riboflavin; Humans